Wage Moderation in France - Estevao, Marcello (IMF Working Papers; Working Paper, 2002)
Using household level data for France from 1990 to 2000, we estimate a relationship between wages and unemployment taking into account compositional, time and regional effects. We show that this relationship shifted outward during the 1990s most likely because of a structural change in workers' behavior, id est "wage moderation". The outward shift was particularly large between 1996 and 2000 and undoubtedly contributed strongly to the exceptional employment performance during that period.